2009
DOI: 10.1007/s10722-008-9397-8
|View full text |Cite
|
Sign up to set email alerts
|

Data analysis for molecular characterization of plant genetic resources

Abstract: Characterizations of plant genetic resources based on molecular markers have been increased in the last years. Studies using a broad range of markers applied on hundreds of plant species are the theoretical basis for inferring genetic diversity to propose both breeding and conservation strategies. Despite increased importance of molecular characterization in plant genetic resources, there is scarce information about analysis of this type of data. To fill this gap of information, this review discuss the rationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
1
13

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(78 citation statements)
references
References 118 publications
2
62
1
13
Order By: Relevance
“…Therefore, large differences between observed and the effective number of alleles indicate low frequencies of a few alleles because they are present in only one or a few genotypes. For this reason, estimate of effective number of alleles could be useful in indicating rare alleles (Laurentin, 2009). In the present study, large differences between the estimates of observed and the effective number of alleles indicate relatively low frequency of a few alleles, which could be considered as rare alleles.…”
Section: Allelic Richness and Discriminating Ability Of Ssr Markersmentioning
confidence: 58%
See 1 more Smart Citation
“…Therefore, large differences between observed and the effective number of alleles indicate low frequencies of a few alleles because they are present in only one or a few genotypes. For this reason, estimate of effective number of alleles could be useful in indicating rare alleles (Laurentin, 2009). In the present study, large differences between the estimates of observed and the effective number of alleles indicate relatively low frequency of a few alleles, which could be considered as rare alleles.…”
Section: Allelic Richness and Discriminating Ability Of Ssr Markersmentioning
confidence: 58%
“…While investigating the diversity of related genotypes in predominately self-pollinated crops such as dolichos bean where only homozygous genotypes were used in the study, Simple Matching Coefficient (SMC) is the most appropriate diversity measure as it takes care of absence of the amplicons in addition to presence of the amplicons in both the compared genotypes as causes of similarity (Laurentin, 2009 (Tanksley and McCouch, 1997).…”
Section: Inter-genotypic Differentiationmentioning
confidence: 99%
“…Relevant applications include the identification of diverse parental combinations to create segregating progeny with maximum genetic variability, introgression of desirable genes from diverse germplasm into the available genetic base, identification of adaptation patterns by linking genetic variability to environmental data, understanding the genetic relationships between major groups of inbred lines used in crosses, assigning inbred lines to specific heterotic groups, and plant varietal protection (Mohammadi and Prasanna, 2003;Reif et al, 2005;Jombart et al, 2009;Laurentin, 2009). The observed genetic diversity is affected by the data (morphological, biochemical, and molecular marker data), the sample size of markers and individuals genotyped, the criterion for defining the optimal number of groups, and the amount of data lost (Mohammadi and Prasanna, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Monitoring forest maintenance by satellites has been criticized because it would not be enough to measure the size of the preserved forest area, but real diversity is not perceived. Species identification must be done in situ (Fonseca et al, 2008), and molecular markers distributed along the genome and not linked to the special selected traits may provide general diversity measures as the number of alleles per locus, as well as the population structure (Laurentin, 2009). …”
Section: Microrganisms and Pests Associated To Plantsmentioning
confidence: 99%